2018
DOI: 10.1111/jdv.15020
|View full text |Cite
|
Sign up to set email alerts
|

Tretinoin (0.05% cream vs. 5% peel) for photoaging and field cancerization of the forearms: randomized, evaluator‐blinded, clinical trial

Abstract: Background Topical tretinoin cream is the gold standard treatment for skin ageing, particularly photoaging. The purpose of tretinoin peel was to obtain similar results, but in a shorter time, however, there have been few controlled trials on its effectiveness. Objective To compare efficacy and safety of tretinoin 0.05% cream and 5% as a peeling agent on photoaging and field cancerization of the forearms. Methods Clinical trial with therapeutic intervention, prospective, randomized (computer‐generated randomiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…Hence, eight studies with an overall sample size of n = 170 (range 13–32) were included in our systematic review (Table 1). 16–23 The studies were published between 1995 and 2018 and were four RCTs, two non‐randomized controlled trials and two single‐arm studies.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, eight studies with an overall sample size of n = 170 (range 13–32) were included in our systematic review (Table 1). 16–23 The studies were published between 1995 and 2018 and were four RCTs, two non‐randomized controlled trials and two single‐arm studies.…”
Section: Resultsmentioning
confidence: 99%
“…Tretinoin, another vitamin A derivative, has been shown to reverse the effects of photoaging, with a 23–60% progressive reduction in actinic keratoses due to cumulative UVR exposure. This effect is attribuTable to a reduction in the stratum corneum and restoration of the dermis within 120 days of treatment ( 12 , 13 ). This may perhaps explain why the 90-day observation period used in the present study was insufficient; use of the barrier cream for a longer period might have allowed the full effect of the retinol component to manifest itself, with the possibility of complete remission of AC lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin-based therapies have been used to reverse cutaneous photodamage and in the treatment of field cancerization ( 12 , 13 ), with particularly promising results for vitamin A analogs. Applied topically, retinoic acid and other metabolites of vitamin A have been used to Fight the signs of photoaging and are capable of reversing the photodamage caused by excessive sun exposure, especially in actinic keratoses; furthermore, they are safe for long-term use ( 12 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…pain, inflammation, hypopigmentation, scarring), treatment availability, and cost. Two recent studies have suggested that 0.05% tretinoin cream may be a good choice to intercalate with classic treatments such as imiquimod and ingenol mebutate in the treatments of AKs 9 and in the improvement of photoaging and stabilization of field cancerization, 10 although another large randomized study of a topical 0.1% tretinoin versus matching vehicle demonstrated that high-dose topical tretinoin was ineffective at reducing the risk of keratinocyte carcinoma. 11…”
Section: Introductionmentioning
confidence: 99%